2020
DOI: 10.1038/s41398-020-00900-8
|View full text |Cite
|
Sign up to set email alerts
|

Citalopram-induced pathways regulation and tentative treatment-outcome-predicting biomarkers in lymphoblastoid cell lines from depression patients

Abstract: Antidepressant therapy is still associated with delays in symptomatic improvement and low response rates. Incomplete understanding of molecular mechanisms underlying antidepressant effects hampered the identification of objective biomarkers for antidepressant response. In this work, we studied transcriptome-wide expression followed by pathway analysis in lymphoblastoid cell lines (LCLs) derived from 17 patients documented for response to SSRI antidepressants from the Munich Antidepressant Response Signatures (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…For the latter, a study in rats had shown that its expression variation was during the molecular signature at the level of the frontal cortex characterizing the AD action of quetiapine in a chronic stress model in rats [ 137 ]. Recently, a study on lymphoblastoid cell lines from depression patients treated with citalopram reported a significant association of NFIB expression with improvement in depression scale [ 138 ]. The NMDA subtype of glutamate receptors (NMDAR) plays a key role in synaptic plasticity in the context of depression [ 139 ], and it has been shown that a Ca 2+ /calmodulin-dependent Ras-guanine-nucleotide-releasing factor (RasGRF1) served as an NMDAR-dependent regulator of the ERK kinase pathway.…”
Section: Discussionmentioning
confidence: 99%
“…For the latter, a study in rats had shown that its expression variation was during the molecular signature at the level of the frontal cortex characterizing the AD action of quetiapine in a chronic stress model in rats [ 137 ]. Recently, a study on lymphoblastoid cell lines from depression patients treated with citalopram reported a significant association of NFIB expression with improvement in depression scale [ 138 ]. The NMDA subtype of glutamate receptors (NMDAR) plays a key role in synaptic plasticity in the context of depression [ 139 ], and it has been shown that a Ca 2+ /calmodulin-dependent Ras-guanine-nucleotide-releasing factor (RasGRF1) served as an NMDAR-dependent regulator of the ERK kinase pathway.…”
Section: Discussionmentioning
confidence: 99%